Ruthenium(ii) complexes as bioorthogonal two-photon photosensitizers for tumour-specific photodynamic therapy against triple-negative breast cancer cells. Issue 36 (6th April 2021) - Lin, Mingwei; Zou, Shanshan; Liao, Xinxing; Chen, Yu; Luo, Diqing; Ji, Liangnian; Chao, Hui
Abstract : We developed the first Ru(ii ) complex-based bioorthogonal two-photon photosensitizers. Through bioorthogonal labelling, they realize effective tumour-specific photodynamic therapy against triple-negative breast cancer cells. Abstract : Herein, we developed the first Ru(ii ) complex-based bioorthogonal two-photon photosensitizers. Through bioorthogonal labelling, they realize effective tumour-specific photodynamic therapy against triple-negative breast cancer cells.